LC-MS/MS identification of the principal in vitro and in vivo phase I metabolites of the novel thiosemicarbazone anti-cancer drug, Bp4eT - Stariat, Ján; Sesták, Vít; Vávrová, Kateřina; Nobilis, Milan; Kollárová, Zuzana; Klimeš, Jiří; Kalinowski, Danuta S; Richardson, Des R; Kovaříková, Petra (Analytical and bioanalytical chemistry, 2012)
The iron chelator, 2-benzoylpyridine-4-ethyl-3-thiosemicarbazone (Bp4eT), was identified as a lead compound of the 2-benzoylpyridine thiosemicarbazone series, which were designed as potential anti-cancer agents. This ligand has been shown to possess potent anti-proliferative activity with a highly selective mechanism of action. However, further progress in the development of this compound requires data regarding its metabolism in mammals. The aim of this study was to identify the main in vitro and in vivo phase I metabolites of Bp4eT using liquid chromatography tandem mass spectrometry (LC-MS/MS). Two metabolites were detected after incubation of this drug with rat and human liver microsomal fractions. Based on LC-MS(n) analysis, the metabolites were demonstrated to be 2-benzoylpyridine-4-ethyl-3-semicarbazone and N (3)-ethyl-N (1)-[phenyl(pyridin-2-yl)methylene]formamidrazone, with both resulting from the oxidation of the thiocarbonyl group. The identity of these metabolites was further shown by LC-MS/MS analysis of these latter compounds which were prepared by oxidation of Bp4eT with hydrogen peroxide and their structures confirmed by nuclear magnetic resonance and infrared spectra. Both the semicarbazone and the amidrazone metabolites were detected in plasma, urine, and feces after i.v. administration of Bp4eT to rats. In addition, another metabolite that could correspond to hydroxylated amidrazone was found in vivo. Thus, oxidative pathways play a major role in the phase I metabolism of this promising anti-tumor agent. The outcomes of this study will be further utilized for: (1) the development and validation of the analytical method for the quantification of Bp4eT and its metabolites in biological materials; (2) to design pharmacokinetic experiments; and to (3) evaluate the potential contribution of the individual metabolites to the pharmacodynamics/toxico-dynamics of this novel anti-proliferative agent.
Keywords: Male; Magnetic Resonance Spectroscopy; Animals; protinádorové látky; chromatografie kapalinová; Humans; Solid Phase Extraction; Antineoplastic Agents; Spectrophotometry, Infrared; mužské pohlaví; spektrofotometrie infračervená; tandemová hmotnostní spektrometrie; krysa rodu Rattus; Thiosemicarbazones; Rats; thiosemikarbazony; Tandem Mass Spectrometry; magnetická rezonanční spektroskopie; techniky in vitro; zvířata; extrakce na pevné fázi; Chromatography, Liquid; lidé; In Vitro Techniques